(untitled) (Journal of Environmental Science and Natural Resources, 2017)
Considering the threatened status, economic and nutritional importance of stinging catfish (Heteropneustes fossilis), a study on larval development was carried out. Hand stripping method of stinging catfish is being practiced in majority of the hatcheries which is not always felicitous in the sense that puts pressure on brood. The study found that, although fertilization rate was higher in stripping method but non-stripping method was concluded better regarding higher hatching rate. The present study recorded the fertilization and hatching rate in hand stripping and non-striping method 62.33±4.51, 46.67±5.86 and 37.33±2.52, 41.33±5.69, respectively. Subsequent embryonic developmental mean time for 2-cell, 4-cell, 8-cell, 16-cell, 32- cell, Morula, Blastula, Germinal ring, Gastrula, yolk plug, twisting movement, and just before hatching was 0.21±0.05, 0.39±0.08, 1.12±0.08, 1.28±0.04, 2.09±0.05, 2.23±0.13, 3.58±0.45, 5.13±0.15, 7.02±0.28, 8.37±0.104, 15.28±1.06, 20.43±2.03 hours, respectively. Results of the current investigation would provide detailed information to the hatchery managers to conduct successful induced breeding strategy of H. fossilis as well as other catfishes. J. Environ. Sci. & Natural Resources, 10(1): 141-148 2017